2013
DOI: 10.1021/la402856j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas or Vapor Adsorption on Adhesion, Friction, and Wear of Solid Interfaces

Abstract: The adsorption of vapor molecules plays an important role in countless fields and is increasingly realized to be critical in tribology, which encompasses adhesion, friction, and wear of surfaces. This feature article reviews experimental methods for quantifying gas and vapor adsorption on flat solid surfaces under equilibrium conditions (ambient pressure and temperature) as well as the effects of these adsorbates on the adhesion, friction, and wear of various materials. Particular attention is given to species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 71 publications
(238 reference statements)
2
48
0
Order By: Relevance
“…The water layer adsorbed on fused quartz ( Fig. 6(a)) behaved like a typical physisorption layer [93,109]. The adsorption of water on soda lime glass differed drastically with three distinct peaks identified at ~3,200, ~3,430, and ~3,680 cm −1 (Fig.…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 96%
“…The water layer adsorbed on fused quartz ( Fig. 6(a)) behaved like a typical physisorption layer [93,109]. The adsorption of water on soda lime glass differed drastically with three distinct peaks identified at ~3,200, ~3,430, and ~3,680 cm −1 (Fig.…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 96%
“…The ethanol adsorbate can not only prevent the formation of Si substrate -O-Si tip bonded bridges during rubbing process, but also increase the energy barrier of Si-O-Si bonds dissociation on silicon surface [22]. Since the adsorption of longer chain molecule may further increase the energy barrier of Si-O-Si bonds dissociation on silicon substrate, the propanol or butanol vapor may have a better capability to resist the tribochemical wear of silicon surface [22,42,43].…”
Section: Lubrication Of Adsorbate Ethanol Layermentioning
confidence: 99%
“…In addition, the slurry is another factor that has a significant effect on the polishing environment and makes the polishing process more complex [12−14]. As one of the simple but key components of a slurry, water not only carries the other components but also acts as an efficient lubricant, which affects the friction and wear behavior of the polished surface, material removal rate, and quality of the polished surface [15]. By studying the nanoscale friction and wear properties of silicon wafer, Chen et al found that the wear rate and friction coefficient in water lubrication were lower and smaller, respectively, than those under dry friction conditions, and the wear mechanism of water lubrication was considered to be a molecule-scale removal process [16].…”
Section: Introductionmentioning
confidence: 99%